EFEKTIVITAS PENEGAKAN HUKUM PELANGGARAN LALU LINTAS MELALUI TILANG MANUAL DAN ELEKTRONIK DI WILAYAH POLDA RIAU - Amelia, Dinda; Dinata, Umar; Yuniarti, Rahmi; Berlian, Cheny (JOURNAL EQUITABLE, 2024)
Frequent traffic violations have made the National Police Traffic Corps in the era of globalization increasingly innovate in prosecuting traffic violations to make it easier for the public to understand the electronic-based ticketing procedures that have just been launched. In Riau Province, currently several districts have implemented electronic-based ticketing, such as Dumai, Indragiri Hilir, Bengkalis, Pelalawan, Siak and Pekanbaru City. The formulation of the problem in this research is related to the effectiveness of law enforcement for traffic violations through manual and electronic ticketing in the Riau Regional Police area and the factors that influence the effectiveness of law enforcement for traffic violations through manual and electronic ticketing in the Riau Regional Police area. This research uses the Empirical Juridical method with a field research approach. The research results show that the implementation of an electronic ticketing system is generally more effective in increasing road user compliance compared to a manual ticketing system. This is caused by several factors, including: the more objective nature of enforcement, wider reach, and the lack of direct interaction between officers and violators which can minimize the potential for fraudulent charges. Effective traffic law enforcement is expected to increase public discipline in traffic, thereby reducing the number of traffic accidents and realizing security and safety on the highway.